The Influence of Innovation Characteristics to Farmers’ Decision in Accepting Integrated Crop-Livestock Technology in Karanganyar Region, Central Java - Sutrisno Hadi Purnomo; Eka Handayanta; Aqni Hanifa; Agung Wibowo; Mela Purnaningrum (Buletin Peternakan, 2019)
Farmer’s decision in accepting integrated crop-livestock farming technology was affected by a some factors, including innovation characteristic. This research aimed to figure out the influence of innovation characteristic (relative advantage, compatibility, complexity, triability and observability) to farmer’s decision in adopting the innovation. The research was held in Ngargoyoso Subdistrict, Karanganyar Region, Central Java Province. Basic method used in this research was descriptive quantitative using purposive sampling technique to determine research location. Samples were determined using purposive sampling method with total number was 52 respondents. Data were analyzed using several analysis : data normality, validity, reliability, Oneway ANOVA, multiple linear regression and classic assumption. Oneway ANOVA test showed that farmers with different farming experience had different response in deciding to adopt the technology. Multiple linear regression test gave an equation Y = 2.379 + 0.369X1 + 0.213X2 + 0.080X3 + 0.777X4+ (-0.320X5) + e. The determination coefficient value (R2) is 0.647. The conclusion of this research was characteristic of innovation significantly influenced the farmers’ decision in accepting the integrated crop-livestock technology simultaneously, but partially only variable relative advantage and triability which significantly influenced to farmers’ decision in accepting the integrated crop-livestock technology innovation.